Associations of Children’s Active School Travel with Perceptions of the Built Environment: Preliminary Study - Osman, Naimah; Nasrudin, Na’asah; Ayu Abdullah, Yusfida (International Journal of Psychosocial Rehabilitation, 2020)
Walking is a healthy way for children to explore the environment and enable them to be more independent. However, nowadays, children prefer using passive modes of transport to commute to school. Hence, it is essential to know the built environment factors that influence children to choose walking as a mode of traveling to school. This study identifies and evaluates the built environment factors that contribute towards children's preference when walking to school. This study, therefore, investigates children's preferences through the schoolchildren themselves to understand their perceptions on the choice to walk to school. Through a case study method, 100 primary school children who walk to school in Sekolah Kebangsaan Seksyen 7, Shah Alam, were selected as respondents. The survey included inquiries on children's background and the homeschool path provisions in terms of quality of pedestrian facilities and surrounding environment. An observation survey was also conducted to identify the availability and conditions of several built environment elements in the study area. Hence, the result of this study will assist town planners when planning for pedestrians, specifically for primary school children.